The management of On-the-job training through web-based application at Vocational High School (SMK) in network computer engineering majors - Suryono, Tito; Wibawanto, Hari; Samsudi, Samsudi (Universitas Sebelas Maret, 2018)
Multiple system education in SMK through On-the-job training is an effort to increase graduate quality in industrial capability. The stages of this research are data collection stage (introduction), system development stage, and evaluation phase (testing). This study, which is research and development, aims to know the feasibility and practicality of the design of web-based applications.The research was conducted at State Vocational High School (SMK Negeri) Jumantono Karanganyar particularly in majors of network computer engineering which involved 12 students of small trial group and 109 students of large-scale test.The data collection method used was observation, documentation, and questionnaire. The data obtained were then analyzed by descriptive analysis technique. The result of black box test done by using 43 items was in accordance with its function. The application expert's validation of this research was 88% meaning that it was very reasonable criteria. Meanwhile, the validation of substance was 89% meaning that it was very feasibleThe result of the usability test for the small-scale group was 68% then, it was improved and tested on a large scale that resulted 85% and was considered as practical. Thus, it can be concluded that the development of web-based On-the-job training management applications is very feasible and practical to be used On-the-job training management in SMK. It is suggested that the use of On-the-job training applications must be intensified.